Impact of Female Obesity on Cumulative Live Birth Rates in the First Complete Ovarian Stimulation Cycle - Ding, Wen; Zhang, Fu-li; Liu, Xiao-cong; Hu, Lin-li; Dai, Shan-jun; Li, Gang; Kong, Hui-juan; Guo, Yi-hong (Frontiers in Endocrinology, 2019)
Background: Female overweight/obesity has been reported to be associated with compromised pregnancy outcomes in fresh embryo transfer cycles. It is unclear whether the cumulative live birth rate (CLBR) is adversely affected after all viable embryos are transferred from the first ovarian stimulation cycle. Objectives: To investigate whether the CLBR was compromised in obese women. Method: A total of 9,972 young women underwent their first IVF/ICSI cycles from January 2012 to October 2017. Pregnancy outcomes were compared according to female BMI. Results: Among 1,671 women with polycystic ovary syndrome (PCOS), those with a BMI ≥28kg/m2 had a lower cumulative clinical pregnancy rate (CCPR) and CLBR during the first complete ovarian stimulation cycle. Additionally, the pregnancy loss rate was increased in this group, although the difference was not significant. Among the 8,101 women without PCOS, the CCPR and CLBR of obese patients was also significantly decreased, and this group also showed increased pregnancy loss rates. Moreover, overweight women also had a decreased CLBR. Conclusions: Female obesity adversely affected the CLBR after utilizing the viable embryos after first oocytes retrieval.